Chromebookgate: Normalisation Of Procurement Fraud And Its Impact On The Acceptance Of Educational Technology - Edih Abdul Hamid; Tuntun Ariadi Sukanta (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study examines the Chromebookgate procurement scandal in Indonesia as a case of corruption-driven public sector fraud and its implications for the adoption of educational technology. Using a qualitative-conceptual approach with a case study strategy, the research relies on secondary data from audit reports, anti-corruption investigations, government documents, media coverage, and recent academic literature. The analysis is conducted within the frameworks of Broken Window Theory and the Technology Acceptance Model (TAM). The findings identify three major forms of fraud: price mark-up, non-compliance with technical specifications, and procedural irregularities involving conflicts of interest. These practices were tolerated and normalized within procurement governance, illustrating a “broken window” effect in which minor violations escalated into systemic corruption. Furthermore, the fraud undermined technology adoption in schools by reducing perceived usefulness, lowering perceived ease of use, and eroding public trust key constructs of TAM. The study contributes theoretically by integrating criminological and information systems perspectives to explain how procurement fraud not only generates financial losses but also diminishes the effectiveness of digital education policies. Practically, the results highlight the importance of zero tolerance toward procurement irregularities, the integration of technology acceptance evaluation in auditing, and stronger transparency and stakeholder participation in procurement governance. These insights are relevant for policymakers, auditors, and practitioners seeking to strengthen anti-fraud mechanisms and ensure the sustainability of digital transformation in education).